Mental health and psychosocial support for the internally displaced persons in Bannu, Pakistan. Issue 1 (March 2016) - Humayun, Asma; Azad, Nadia; Haq, Israr ul; Khan, Faisal Rashid; Ahmad, Ambreen; Farooq, Rai Khalid
Abstract : Following armed conflict in the North Waziristan Agency, a mental health and psychosocial support initiative was launched for internally displaced persons in Bannu, Pakistan. This was convened by volunteer mental health professionals, in collaboration with a variety of agencies (provincial government, military, humanitarian agencies) in a security compromised region. As part of the initiative, monthly camps were held for a period of six months. Mental health needs were assessed. A multidisciplinary team (psychiatrists, psychologists, psychiatric nurses and psychosocial workers) offered mental health care to 680 people who attended the camps, of which 28% were under the age of 18 years old. Twenty-one percent returned for follow-up, while others were followed-up in the community by psychosocial teams. Estimates of common mental disorders were found. Both pharmacological and psychological treatments were offered, according to existing guidelines. Active efforts were made to conduct holistic assessments and avoid a pure biomedical approach. This also provided an opportunity for training non specialist staff and led to formal (World Health Organization) mental health gap action plan training for primary care staff.